Advanced Epithelioid Malignant Peripheral Nerve Sheath Tumor Showing Complete Response to Combined Surgery and Chemotherapy: A Case Report - Tomohiro Minagawa; Ryuta Shioya; Chigusa Sato; Ryuji Shichinohe; Go Yasui; Kohsuke Ishikawa; Hiroko Takahashi (Case Reports in Oncological Medicine)
Malignant peripheral nerve sheath tumor (MPNST) is a rare high-grade soft tissue sarcoma. The epithelioid variant accounts for 5% or less of MPNSTs; the clinical behavior of this variant is unclear. Reports of approximately 40 cases are available in the English literature; however, most reports addressed clinicopathological features rather than therapeutic procedures or clinical courses. We describe a case of a 62-year-old male with an epithelioid MPNST of the left foot. Multiple lung metastases developed after radical surgery on the primary lesion. The response to adjuvant chemotherapy including doxorubicin and ifosfamide was favorable, and thoracoscopic resection was subsequently performed on the remaining three metastases. No evidence of recurrence or metastasis was observed at the 12-month followup after the first operation. Further followup and chemotherapy may be required.